2010
DOI: 10.1007/s10643-010-0373-5
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration of Teacher Education and Child Disability Health Care: Transdisciplinary Approach to Inclusive Practice for Early Childhood Pre-Service Teachers

Abstract: The purpose of this paper is to describe the collaborative efforts between an Early Childhood Teacher Education Program and a Child Disability Health Care Program to incorporate a transdisciplinary model in the preparation of early childhood teachers in inclusive practice. Recent studies suggest essential components of teacher preparation in early childhood inclusion include: helping students construct a positive image of inclusive practice, incorporating a family-centered approach, and collaborating and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 5 publications
(12 reference statements)
1
10
0
3
Order By: Relevance
“…This finding is comparable to those in other studies that indicated additional inclusive education training was associated with teachers feeling more self-efficacious (Ching et al, 2007;Kyriakou et al, 2007;Silverman et al, 2010). The results also revealed that younger teachers had significantly more positive attitudes toward including the learner with LNFS in their classroom and more positive attitudes regarding the learner with ADHD in general.…”
Section: [T] Insert Table 5 Near Here/[t] Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This finding is comparable to those in other studies that indicated additional inclusive education training was associated with teachers feeling more self-efficacious (Ching et al, 2007;Kyriakou et al, 2007;Silverman et al, 2010). The results also revealed that younger teachers had significantly more positive attitudes toward including the learner with LNFS in their classroom and more positive attitudes regarding the learner with ADHD in general.…”
Section: [T] Insert Table 5 Near Here/[t] Discussionsupporting
confidence: 86%
“…Teachers who receive additional training about inclusive education, however, have more positive attitudes concerning inclusion when compared to teachers who have not had such training (Silverman et al, 2010). Moreover, research has found that after taking a professional development course in inclusive education, teachers evidenced a positive change in attitudes about including learners with special needs in their class (Ching, Forlin, & Mei Lan, 2007; Kyriakou, Avramidis, Hoie, Stephens, & Hultgren, 2007).…”
Section: Teachers' Attitudes About Learners With Barriers To Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Our journey with these two children confirmed earlier literature emphasising the need to incorporate a parent- or family-centred approach (Dunst, Bruder, Trivette & Hamby, 2006 ; Turnbull, Summers, Turnbull et al . 2007 ); to assist the relevant teachers towards a positive attitude to inclusive education and to build strong interdisciplinary collaborations (Silverman, Hong & Trepanier-Street 2010 ). Here, it resulted in different outcomes for the two children; one child was eventually integrated into a mainstream primary school in his area, while the other child was integrated into a boarding school for learners with special educational needs (an ‘LSEN school’ 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Family centred approaches. Luger et al (2012) highlight the importance of a parent-or familycentred approach (Dunst et al, 2006;Turnbull et al, 2007); to enable transition to school for children with disabilities and to build strong interdisciplinary collaborations (Silverman et al, 2010).…”
Section: Support Systemsmentioning
confidence: 99%